2021
DOI: 10.1038/s41526-021-00163-7
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase HDA-4-mediated epigenetic regulation in space-flown C. elegans

Abstract: Epigenetic changes during long-term spaceflight are beginning to be studied by NASA’s twin astronauts and other model organisms. Here, we evaluate the epigenetic regulation of gene expression in space-flown C. elegans by comparing wild type and histone deacetylase (hda)-4 mutants. Expression levels of 39 genes were consistently upregulated in all four generations of adult hda-4 mutants grown under microgravity compared with artificial Earth-like gravity (1G). In contrast, in the wild type, microgravity-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The gene expression in Caenorhabditis elegans was investigated in a series of experiments on the ISS: the results showed a downregulation of genes related to longevity [ 96 ] or metabolism and protein expression [ 89 ]. The most recent results indicate that the expression is partially regulated epigenetically: an overexpression of several genes was observed in histone deacetylase (had)-4 mutants as compared to wild types, indicating that in a wild-type organism, excessive expression of certain genes is epigenetically suppressed to the extent of a de facto downregulation, while in the had-4 mutant, the overexpression occurs unhampered ( Table 2 ) [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression in Caenorhabditis elegans was investigated in a series of experiments on the ISS: the results showed a downregulation of genes related to longevity [ 96 ] or metabolism and protein expression [ 89 ]. The most recent results indicate that the expression is partially regulated epigenetically: an overexpression of several genes was observed in histone deacetylase (had)-4 mutants as compared to wild types, indicating that in a wild-type organism, excessive expression of certain genes is epigenetically suppressed to the extent of a de facto downregulation, while in the had-4 mutant, the overexpression occurs unhampered ( Table 2 ) [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…To further extend our exploration from cell culture to the whole-body level, we used nematode samples flown in the ISS 16 . The L1 larvae were cultured under microgravity conditions for 4 d, while the control worms were incubated in a 1 × g centrifuge (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the samples were stored in a Minus Eighty degree Celsius Laboratory Freezer for ISS (MELFI) at −95°C. Samples were returned to the ground by SpaceX CRS-22 (SpX-22) in July 2021, maintaining their frozen status, and were stored at −80°C in the laboratory for ribosome profiling and RNA-seq.. Space-flown C. elegans samples prepared for earlier experiments ( 16 ) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that C. elegans overall body length is smaller in space [ 20 , 26 ]. Thus, one possibility is that the smaller muscle area observed in space may be due to growth limitations in the space environment and overall smaller body size.…”
Section: Resultsmentioning
confidence: 99%